Pengharapan Kosmis Dan Pneumatology dalam Penderitaan: Analisis Eskatologi “Sudah dan Belum” Roma 8:18-30 - Wenny Kartika Susanto (Sekolah Tinggi Alkitab Penyebaran Injil (STAPIN) Majalengka, 2026)
Faith in Jesus Christ constitutes the foundation of justification and salvation in Christianity. Nevertheless, believers continue to live within the reality of a world that remains under the influence of sin. This article aims to examine cosmic hope and the role of the Holy Spirit in suffering through the framework of the